Legal aspects of a healthy diet for children. Comments on the grounds of the directive on foodstuffs in schools - Urbaniak, Monika (Journal of Medical Science, 2015)
The aim of this article is to analyze legal solutions for the availability of foodstuffs in schools, binding from Sep 1, 2015, targeted to introduce into school shops and canteens so-called healthy food. The Directive issued by the Minister of Health on Aug 26, 2015 on groups of foodstuffs intended to be sold to children and young people in education system units and requirements for foodstuffs used within collective feeding of children and young people in those units eliminated from school shops provide a list of food which is considered unhealthy. The adopted solutions are an introduction to the legal statutory fight against obesity in children and young people and enhance the protection of the health of children at pre-school and school age by limiting access within kindergartens, schools and tutelary-educational institutions to foodstuffs containing significant quantities of ingredients not recommended for their development.
Keywords: food; obesity; liberty of economic activity; children and young people